(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
So with acceptance of this challenge here we studied an Ayurvedic medicine ‘Sinhamrit Ghruta’ mentioned in Yogartnakara in Vataja Pramehachikitsa. A single case study was done on use of Sinhamrut Ghruta in Vataja Prameha (Diabetes mellitus) and clinical and pathological assessment was done. Pathological criteria which are mostly used for diagnosis of Diabetes mellitus i.e. blood and urine sugar levels and HbA1c were assessed before and after treatment of patients. Most of the symptoms present in Vataja Prameha are due to predominantly vitiated Vata and Pitta. Both of them cause dryness and undernourishment of Strotas as the micro capillaries which carries nutrition to various body constituents. Ghruta used in this medicine is majorly Snigdha by nature that causes Sneha of dry capillaries and it decreases Vata and Pitta. Also in addition to this contents of Snihmrut Ghrita are Rasayana i.e., nutritive to each and every body constituent. In this way after using Sinhamrit Ghruta for 15 days in the patient we found significant changes in clinical and pathological status of patient. However this study is a very basic guidance to illuminate the pathway to the treatment of Diabetes mellitus. More observation is being studied in larger group and for long duration.